Analisis Ketidakstabilan Lereng Berdasarkan Nilai Suseptibilitas Magnetik (Studi Kasus: Dua Lereng di Nagari Sikucur Tengah, Padang Pariaman) - Mulia, Bagas Meiza; Budiman, Arif (Universitas Andalas, 2025)
A study has been conducted for slope instability analysis based on magnetic susceptibility values ​​in Nagari Sikucur Tengah, Padang Pariaman. Soil sampling was carried out on two tracks from slopes without vegetation (Path A) and slopes with vegetation (Path B) and one reference point. Measurement of magnetic susceptibility values ​​of samples using the Bartington Susceptibility Meter using two frequencies, namely low frequency (lf) and high frequency (hf). Based on the magnetic susceptibility value at low frequency (κlf), it was obtained that the magnetic minerals that control the reference point samples are ferrimagnetic, while samples from Path A and Path B are ferrimagnetic and paramagnetic, but some samples from Path B are ferrimagnetic. The relationship between the κlf value and the depth at the reference point shows a consistent pattern of decreasing values, while Path A and Path B fluctuate and the κlf value at Path A is much smaller than Path B from the reference point. Based on the frequency-dependent susceptibility value κfd, the sample of Path A is dominated by superparamagnetic domains, indicating that the sample has much smaller grains than the sample of Path B. Both slopes have experienced instability, where the slope of Path A has experienced higher instability than the slope of Path B.